UJI EFEKTIVITAS EKSTRAK KUNYIT SEBAGAI ANTIBAKTERI DALAM PERTUMBUHAN Bacillus sp dan Shigella dysentriae SECARA IN VITRO - Yuliati, Yuliati (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2016)
Turmeric is a spice plants that acts as an antibacterial, because it contains a variety of compounds including curcumin and essential oil. Essential oils can be used as an antibacterial because it contains hydroxyl and carbonyl functional group which is phenols derivative. Te phenol derivatives will interact with the bacterial cell wall, then absorbed and penetrated into the bacterial cell, causing precipitation and denaturation of proteins, the result will lyse the bacterial cell membrane, while the antibacterial activity of curcuminis by inhibiting bacterial cell proliferation. Turmeric has launched a pharmacological eﬀect, lowering the fat content, asthma , hepatitis , anti- gall , anti- inﬂammatory , anti- diarrhea , and act as anti-inﬂammatory or anti-inﬂammatory. Turmeric has antibacterial properties of curcumin and essential oil that is capable of inhibiting the growth of bacteria that causes diarrhea and Shigelladysenteriae Bacillus sp. Tis study was conducted to determine the eﬀectiveness of turmeric extract on the growth of Bacillus sp and Shigella dysenteriae, with various concentrations of 15%, 30%, 50%, 75%, and 100% by the well diﬀusion method. Based on theinhibition zone measurement of bacteria Bacillus sp and Shigella dysenteriaethe results were weak category, for the bacteria Bacillus sp with a concentration of 15 % , 30 % , 50 % , 75 % , and 100 % with a diameter of 11 ; 12.3 ; 13 , 3 ; 13.7 ; 14.7 mm, while for the bacteria Shigella dysenteriae with the same concentration has a diameter of 10.3 ; 11.7 ; 12.3 ; 13.3 , and 14.7 mm. Te conclusion of the study is that the antibacterial activity of turmeric extract is more effective against the bacteria Bacillus spthan against bacteria Shigella dysenteriae, although the diﬀerence was not signifcant.